Cointegration and Exogeneity in Eurobanking and Latin American Banking: Does Systemic Risk Linger? - Simpson, John (Blackwell Publishing, 2008)
This paper examines financial integration, interdependence and exogeneity within and between Latin American banking and Eurobanking systems during a period of relative stability after the oil and debt crises of the 1980s. Significant evidence of cointegration in both long and short-term relationships is reported. Within Latin America, exogeneity lies mainly with the Brazilian system. Within Eurobanking, the U.S. system is dominant influence. Between Eurobanking and Latin American banking systems, the U.S. system is the major driving force. With continued interdependence of these banking systems, systemic risk lingers and vigilance is required in banking supervision.